لتعليم مهارة القراءة SQ3R تطوير المواد التعليمية على أساس طريقة - Satni; Trinurhadi, Tandri; Jumhana, Nana (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2022)
This study aims to determine the development of teaching materials based on the SQ3R method (Survey, Question, Read, Recite, Review) for teaching reading skills in the tenth grade of MA Al-Mahdi Sindangheula, to determine the effectiveness of their use, and to determine their feasibility. To achieve the above related objectives, the researcher uses Brog and Gall's theory of development in six steps: needs and problem analysis, data collection, product design, product validation, product improvement, and product testing. The effectiveness of teaching materials based on the SQ3R method for teaching reading skills is based on the results of the pre-test 34.2% and post-test 75.2%. These results show that there is an increase with a large difference of 41%. Based on these results indicate that the use of teaching materials based on the SQ3R method for teaching reading skills is effective.